Examining the interface between the objectives of competition policy and intellectual property (UN New YorkUS, 2016)
Considers the relationship between intellectual property rights and competition; elaborates on business practices in the exercise of intellectual property rights that create competition-related converns, and addresses ways of dealing with anti-competitive practices related to intellectual property rights.
Keywords: INTELLECTUAL PROPERTY